BRAND EQUITY AND CUSTOMER’S LOYALTY IN HEALTHCARE SETTING: A NARRATIVE REVIEW (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2019)
ABSTRACT Background: The growth of hospitals in the world is getting higher, and over time makes hope for the quality of better health services. Since 2012, in Indonesia, there has been an increase number of hospitals by 5.2%, with the number of hospitals amounting to 2,820 hospitals. The large number of hospitals has made competition between hospitals to attract customers even higher. Hospitals need to think about how to maintain the loyalty of their patients to build hospital’s income. One that influences brand loyalty is brand equity from the service provider. Research objective: The purpose of this study is to assess the influence of brand equity on brand loyalty, and assess the values ​​that affect customer loyalty. Method: The research method is a review of narrative literature using a systematic search, including 11 studies. Result: This brand equity was found to have dimensions such as brand loyalty, brand association, brand awareness, brand trust and perceived quality. Patient loyalty can only be achieved by increasing patient satisfaction through good quality services. Conclusion: Only by a good that patient re-visit intention could be build and in the end increase the hospital's revenue. Keywords: brand equity, brand loyalty, customer loyalty, hospital ABSTRAK Latar belakang: Pertumbuhan rumah sakit di dunia semakin tinggi, dan seiring dengan waktu membuat harapan terhadap mutu pelayanan kesehatan semakin tinggi. Sejak tahun 2012 sampai dengan saat ini, di Indonesia terdapat peningkatan jumlah rumah sakit sebesar 5,2%, dengan jumlah rumah sakit sebesar 2.820 rumah sakit. Banyaknya jumlah rumah sakit membuat persaingan antar rumah sakit untuk menggaet pelanggan pun semakin tinggi. Rumah sakit perlu memikirkan bagaimana mempertahankan loyalitas dari pasien mereka untuk membangun pendapatan rumah sakit. Salah satu yang mempengaruhi loyalitas merek adalah ekuitas merek (brand equity) dari penyedia layanan. Tujuan penelitian: ini adalah menilai pengaruh ekuitas merek terhadap loyalitas merek, dan menilai nilai-nilai yang mempengaruhi loyalitas pelanggan. Metode: Peninjauan literatur naratif menggunakan pencarian sistematik, dengan menyertakan 11 studi. Hasil: Ekuitas merek ini ditemukan memiliki dimensi seperti loyalitas merek, asosiasi merek, kesadaran merek, kepercayaan merek dan kualitas yang dirasakan. Loyalitas pasien hanya dapat dicapai dengan meningkatkan kepuasan pasien melalui layanan berkualitas baik. Kesimpulan: Hanya dengan kepuasan pasien yang baik, niat kunjungan ulang dapat dibangun dan akhirnya meningkatkan pendapatan rumah sakit Kata kunci: ekuitas merek, loyalitas merek, loyalitas pelanggan, rumah sakit